Melatonin receptor 1B gene associated with hyperglycemia in bipolar disorder. (June 2016) - Hukic, Dzana S.; Lavebratt, Catharina; Frisén, Louise; Backlund, Lena; Hilding, Agneta; Gu, Harvest F.; Östenson, Claes-Göran; Erlinge, David; Ehrenborg, Ewa; Schalling, Martin; Ösby, Urban
Abstract : Bipolar patients are at a higher risk of developing metabolic disorders. Cardiovascular morbidity and mortality is twice the rate reported in the population. Antipsychotic medication increases the risk of metabolic abnormalities. However, bipolar disorder and schizophrenia have a similarly increased mortality from cardiovascular causes of death, although bipolar patients medicate with antipsychotic drugs to a much smaller extent than schizophrenic patients. Bipolar disorder and schizophrenia share substantial genetic risk components; thus, increased metabolic abnormalities is hypothesized to be an effect of specific sets of metabolic risk genes, which might overlap with the metabolic risk genes in schizophrenia. This study reports that a functional genetic variant of MTNR1B, previously implicated in the impairment of glucose-stimulated insulin release also in schizophrenia, was associated with elevated fasting glucose levels in bipolar patients and controls. This finding suggests that the MTNR1B -dependent vulnerability for elevated fasting plasma glucose levels is shared between bipolar disorder and schizophrenia.